Constitution of India professional ethics and human rights - Shubham Singla ;[et.al]; Harris,Charles E; Pritchard,Michael S; Rabins,Michael J (Australia Cengage learning India Pvt.Ltd, 2019)
Constitution of India, Professional Ethics and Human Rights is a fundamental book for all those who are seeking to learn about the Constitution of India, identify individual role and ethical responsibility towards society, and understand basic human rights in India and their implications. This book caters to students who are preparing for all types of State/National/Public sector examinations and all other general competitive examinations. At the end of chapters, practice questions with answer keys are given. The concepts are explained in simple and lucid manner for easy understanding of the students and with the perspective of taking up all upcoming competitive examinations. The book ensures coverage of the syllabus in entirety with newly inserted topics about professional ethics/integrity/engineering standards and intellectual property rights (IPR) information......
Keywords: Constitution; Human rights